Proteins from Agri-Food Industrial Biowastes or Co-Products and Their Applications as Green Materials - Estefanía Álvarez-Castillo; Manuel Felix; Carlos Bengoechea; Antonio Guerrero (Foods, 2021)
A great amount of biowastes, comprising byproducts and biomass wastes, is originated yearly from the agri-food industry. These biowastes are commonly rich in proteins and polysaccharides and are mainly discarded or used for animal feeding. As regulations aim to shift from a fossil-based to a bio-based circular economy model, biowastes are also being employed for producing bio-based materials. This may involve their use in high-value applications and therefore a remarkable revalorization of those resources. The present review summarizes the main sources of protein from biowastes and co-products of the agri-food industry (i.e., wheat gluten, potato, zein, soy, rapeseed, sunflower, protein, casein, whey, blood, gelatin, collagen, keratin, and algae protein concentrates), assessing the bioplastic application (i.e., food packaging and coating, controlled release of active agents, absorbent and superabsorbent materials, agriculture, and scaffolds) for which they have been more extensively produced. The most common wet and dry processes to produce protein-based materials are also described (i.e., compression molding, injection molding, extrusion, 3D-printing, casting, and electrospinning), as well as the main characterization techniques (i.e., mechanical and rheological properties, tensile strength tests, rheological tests, thermal characterization, and optical properties). In this sense, the strategy of producing materials from biowastes to be used in agricultural applications, which converge with the zero-waste approach, seems to be remarkably attractive from a sustainability prospect (including environmental, economic, and social angles). This approach allows envisioning a reduction of some of the impacts along the product life cycle, contributing to tackling the transition toward a circular economy.